The observed variability of the cooling and deepening of the mixed layer in the central Arabian Sea during Monsoon-77 - RAO, RR (MAUSAM, 1987)
Heat budget analysis of the mixed layer indicated that the surface cooling of 2.3 ° C in the central Arabian Sea with the onset and sway of the summer monsoon over five weeks during MONSOON- 77 was mostly due to the net ocean surface losses as compared with the contributions of entrainment and advection of colder waters. A major portion of the corresponding mixed layer deepening of 55 m is explained by the one dimensional forcing of surface cooling leading to convective turnover. Under the only forcing of surface net heat loss, simple prognostic calculations simulated the observed cooling with a r.m.s error of 0.1 °C in both the phases and deepening with the corresponding error of 2.8 m and 6.3 m in phases I and II respectively.